The Added Value and Feasibility Analysis of Breadfruit Chips (A Case Study of Bumdes Tabelala Barakati) - Edisut Edisut; Wa Ode Dian Purnamasari; La Ode Muhammad Mustari; Wardana Rifani (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
The abundant breadfruit (Artocarpus altilis) potential in Wabula 1 Village remains underutilized, creating a gap in optimizing local resources for economic improvement. This study assessed the added value and feasibility of processing breadfruit into breadfruit chips at Bumdes Tabelala Barakati. In November 2024, the study used a descriptive and quantitative approach with data collected from a single respondent, the head of Bumdes Tabelala Barakati. Added value analysis utilized the Hayami method, while feasibility was analyzed using the R/C ratio. Results showed an added value of IDR 55,425.54 per kilogram per production period, with a 92% added value ratio, highlighting the significant contribution of processing to product value. The production margin was IDR 56,666.67 per kg. Feasibility analysis confirmed the business viability with a B/C ratio of 2.73.